Hubungan Perilaku Perawatan Payudara Dengan Kelancaran Pengeluaran Asi Pada Ibu Post Partum - Kurniawan, Vendi Eko; Rozi, Fahrur; Astuti, Novy Tri Wahyu (WELL BEING, 2018)
Mostly in mothers postpartum experiencing less milk production and the slow out may cause the mother did not breastfeed her baby enough, the problem of early postpartum breastfeeding is nipple pain, blisters, swollen breasts And there are still many breastfeeding mothers who do not perform breast care, possibility this is causing an insufficient the expenditure of ASI. The purpose of this study is to determine the relationship of behavior breast care with the ASI smoothness of post partum mother in the Kedunglosari village Jombang. The study design used is analytic correlation with cross sectional approach. While the sampling technique used is non-probability sampling method using quota sampling, with 100 people population and the 30 post partum mothers sample. These results indicate that the majority of respondents behave positively in the treatment of breast ammount 16 people (53.3%) and the other half respondents smoothness of ASI ammount 15 people (50%). Data analysis using Spearman Rank Test with significant levelthat is ρ value = 0.002 <α (12:05) so H1there is relationship between breast care with the ASI's smoothness of post partum mothers in Kedunglosari village Jombang. Based on this study, postpartum mothers should all realize that the importance of breast care to avoid the lack of launch expenses ASI.